ASAALIIBU AN-NIDAI MIN AAYAATI AD-DU’AI FII AL-QUR’AN AL-KARIIM (DIRAASAH TAHLIILIYYAH BIL BALAGHIYYAH) - Khairudin (Program Studi Pendidikan Bahasa Arab, 2022)
This research deals with the methods of calling from the supplication verses in the Holy Quran: an analytical study rhetorical. This research aims to study and search for the methods of call that are included in the verses of supplication from The Holy Quran, and the methodology used in this research is desk research, and the type of this research is research descriptive. The results of this research indicate that the verses of supplication come in the form of the command, with the presence of the command verb in them and more This method is used by others. In addition to the imperative form in the supplication verses, the researcher found formulas The other ones that are included in the supplication verses in the Holy Qur’an. Including: the method of prohibition, the style of wishing and the style the condition. The researcher hopes that this research will have benefits for the researcher himself and for those who master a study Quranic. The researcher hopes that there will be someone who will study this research with a deep study to uncover the secrets rhetorical in it.